2016
DOI: 10.1002/asna.201612425
|View full text |Cite
|
Sign up to set email alerts
|

Kinematical properties of coronal mass ejections

Abstract: Coronal mass ejections (CMEs) are the most dynamic phenomena in our solar system. They abruptly disrupt the continuous outflow of solar wind by expelling huge clouds of magnetized plasma into interplanetary space with velocities enabling to cross the Sun-Earth distance within a few days. Earth-directed CMEs may cause severe geomagnetic storms when their embedded magnetic fields and the shocks ahead compress and reconnect with the Earth's magnetic field. The transit times and impacts in detail depend on the ini… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 112 publications
0
6
0
Order By: Relevance
“…The kinematic profiles of these events have been a major focus of research, as they hold clues about the eruption processes that drive CMEs by transforming magnetic into kinetic energy and about the potential effects of the event on space weather (Temmer 2016). Fast CMEs can drive coronal (and inner heliospheric) shocks that accelerate high-energy SEPs that pose a direct threat to space assets and human exploration (Temmer 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The kinematic profiles of these events have been a major focus of research, as they hold clues about the eruption processes that drive CMEs by transforming magnetic into kinetic energy and about the potential effects of the event on space weather (Temmer 2016). Fast CMEs can drive coronal (and inner heliospheric) shocks that accelerate high-energy SEPs that pose a direct threat to space assets and human exploration (Temmer 2021).…”
Section: Introductionmentioning
confidence: 99%
“…One reason for flare‐integrated flux (X‐ray fluence) being more important than flare magnitude for SEP production may be due to it being more closely associated to its corresponding CME characteristics (e.g., CME acceleration; Temmer, ). SPRINTS observation of flare decay‐phase importance for SEP production in the machine‐learning decision tree models is also consistent with Belov et al ().…”
Section: Conclusion and Remarksmentioning
confidence: 99%
“…This is because the local orientation of the magnetic field to the shock front strongly modulates the particle acceleration process (Guo & Giacalone, 2013). Furthermore, it has been shown that often in the early stages of eruptions the CME over-expands in the lateral direction, changing the overall shape of the compressive front ahead of it (Bein et al, 2011;Temmer, 2016). Thus, it is imperative to move beyond the idealized descriptions of the shock surfaces regularly used to model their evolution (Vourlidas et al, 2012;Kwon et al, 2014;Rouillard et al, 2016), and to employ more advanced techniques.…”
Section: Introductionmentioning
confidence: 99%